2017
DOI: 10.1119/1.4974744
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative exams: Cheating? Or learning?

Abstract: Virtually all human activity involves collaboration, and yet, collaboration during an examination is typically considered cheating. Collaborative assessments have not been widely adopted because of the perceived lack of individual accountability and the notion that collaboration during assessments simply causes propagation of correct answers. Hence, collaboration could help weaker students without providing much benefit to stronger students. In this paper, we examine student performance in open-ended, two-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…It is interesting to note that Fig. 7 is very similar to Figure 3 of Jang et al (2017), which is interpreted as "all students (on average) gain from collaborating" (p226). Yet, the present study found that the two-stage exam had no effect on learning (as measured by a delayed post-test).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It is interesting to note that Fig. 7 is very similar to Figure 3 of Jang et al (2017), which is interpreted as "all students (on average) gain from collaborating" (p226). Yet, the present study found that the two-stage exam had no effect on learning (as measured by a delayed post-test).…”
Section: Discussionmentioning
confidence: 63%
“…There are 90 instances of a group responding to a question at stage two, and, following Jang et al (2017), I analyse these with respect to the number of students in the group who were correct at stage one (see Fig. 2).…”
Section: Group Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an opportunity for peer learning, and it is used to clarify concepts that students did not grasp on their own. This practice is sometimes called two-stage cooperative testing, and it has been shown to increase student engagement as well as learning for both the students who knew the material initially and those who did not (Eaton, 2009;Hollis Gilley & Clarkston, 2014;Jang, Lasry, Miller, & Mazur, 2017;Wieman, Riger, & Heiner, 2014;Zipp, 2007). Students repeat the same quiz, but this time they do it in their team and report their answers on an Immediate Feedback-Assessment Tool (IF-AT), an idea I borrowed from team-based learning (Michaelsen, Bauman Knight, & Fink, 2004).…”
Section: Tool 5: Group Quizzes On Homeworkmentioning
confidence: 99%
“…Typically, two-stage exam data are analyzed by comparing the proportions of students with a correct answer for the individual and group portions of the exam as a means of estimating student gains (Cortright et al 2003;Zimbardo et al 2003;Gilley and Clarkston 2014;Fengler and Ostafichuk 2015;Bruno et al 2017;Jang et al 2017). Additionally, several studies revealed two-stage exams had positive effects on student engagement and perceptions of assessments (Cortright et al 2003;Zimbardo et al 2003;Reiger and Heiner 2014;Weiman et al 2014;Bruno et al 2017).…”
Section: Introductionmentioning
confidence: 99%